Marvel-verse rocket & groot ebook - Mantlo, Bill (Marvel-Verse., 2023)
Collects Incredible Hulk (1963) #271, Free Comic Book Day 2014 (Rocket), Rocket Raccoon (2014) #5, Rocket Raccoon and Groot (2016) #4, Groot (2015) #6 and material from A Year of Marvels: The Unbeatable. Rocket and Groot are the most lovable duo in the Marvel-Verse - and these are some of their craziest adventures! Rocket Raccoon blasts his way into action as Guardian of the Keystone Quadrant - just as the Incredible Hulk lands in his jurisdiction! But when Rocket and Groot team up, that's when the fur really flies! Can they rescue a princess with a price on her head? Entertain a group of alien scouts with a campfire story? Tick-off their to-do-list on the mudball named Earth? And hold their own in Tony Stark's intergalactic Fantasy Football League? Plus: Rocket forms an unbeatable bond with Tippy-Toe the squirrel!